Innovation collaboration between family firms and startups: Insights from the German construction industry - Anne Scharmann (Junior Management Science (JUMS), 2024)
Seeking to increase their innovative strength, family firms increasingly collaborate with startups to explore new technologies, act upon trends, and rejuvenate their corporate culture. While family firms usually innovate incrementally, collaborating with startups allows them to take a more radical approach to innovation to explore new business models and enter untapped markets. The present study aims to contribute to the emerging research field around innovation collaboration between family firms and startups by providing insights from the German construction industry. Drawing on the findings of 40 interviews, comprising four exploratory case studies and 24 expert interviews, this study analyzes impediments, mitigation mechanisms, and prospects of family firm startup collaboration in the German construction industry. The findings reveal that impediments emerge before and during collaboration and are influenced by the construction industry's context. Involved organizations address these impediments by leveraging mitigation mechanisms, including trust-building, financial incentivization, stakeholder involvement, and communication. In this way, innovation collaboration with startups can help strengthen family-owned construction companies' future viability in an evolving industry.
Keywords: 330; construction industry; family firm (FF); family firm startup collaboration (FSC); innovation collaboration; startup (SU)